Red flag screening for low back pain: nothing to see here, move along: a narrative review. Issue 8 (18th September 2017) - Cook, Chad E; George, Steven Z; Reiman, Michael P
Abstract : Screening for red flags in individuals with low back pain (LBP) has been a historical hallmark of musculoskeletal management. Red flag screening is endorsed by most LBP clinical practice guidelines, despite a lack of support for their diagnostic capacity. We share four major reasons why red flag screening is not consistent with best practice in LBP management: (1) clinicians do not actually screen for red flags, they manage the findings; (2) red flag symptomology negates the utility of clinical findings; (3) the tests lack the negative likelihood ratio to serve as a screen; and (4) clinical practice guidelines do not include specific processes that aid decision-making. Based on these findings, we propose that clinicians consider: (1) the importance of watchful waiting; (2) the value-based care does not support clinical examination driven by red flag symptoms; and (3) the recognition that red flag symptoms may have a stronger relationship with prognosis than diagnosis.